Use of granulocyte-colony stimulating factor to prevent recurrent clozapine-induced neutropenia on drug rechallenge: A systematic review of the literature and clinical recommendations. (October 2017) - Myles, Nicholas; Myles, Hannah; Clark, Scott R; Bird, Robert; Siskind, Dan
Background: Clozapine is the most effective medication for treatment-refractory schizophrenia; however, its use is contraindicated in people who have had previous clozapine-induced neutropenia. Co-prescription of granulocyte-colony stimulating factor may prevent recurrent neutropenia and allow continuation or rechallenge of clozapine. Objective and methods: Systematic review of literature reporting the use of granulocyte-colony stimulating factor to allow rechallenge or continuation of clozapine in people with previous episodes of clozapine-induced neutropenia. The efficacy of granulocyte-colony stimulating factor and predictors of successful rechallenge will be determined to elucidate whether evidence-based recommendations can be made regarding the use of granulocyte-colony stimulating factor in this context. Results: A total of 17 articles were identified that reported on clozapine rechallenge with granulocyte-colony stimulating factor support. In all, 76% of cases were able to continue clozapine at median follow-up of 12 months. There were no clear clinical or laboratory predictors of successful rechallenge; however, initial neutropenia was more severe in successful cases compared to unsuccessful cases. Cases co-prescribed lithium had lower success rates of rechallenge (60%) compared to those who were not prescribed lithium (81%). The most commonly reported rechallenge strategy was use of filgrastim 150–480 µg between daily to three times a week. There were no medication-specific side effects of granulocyte-colony stimulating factor reported apart from euphoria in one case. Three cases who failed granulocyte-colony stimulating factor had bacterial infection at time of recurrent neutropenia. No deaths were reported. Conclusion: Preliminary data suggest granulocyte-colony stimulating factor is safe and effective in facilitating rechallenge with clozapine. Clinical recommendations for use are discussed.